THE EFFECT OF TAX COMPLIANCE AND TAX AVOIDANCE ON DEFENDER’S BUSINESS STRATEGY IN COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2016-2019 - Theresia, Fransisca; Sitardja, Meco; Wijaya, Fery; Setiono, Bambang (School of Accountancy, University of Agung Podomoro, 2022)
The main purpose of the research is to analyze tax compliance dan tax avoidance on defenderbusiness strategy. This research was a quantitative descriptive research method. The sampel used inthis research is a secondary data of LQ 45 on the periode 2016 to 2019, and based on purposivesampling method was obtained 23 companies. Variabel tax compliance and defender business strategyusing variabel dummy. Variabel tax avoidance using CETR proxy. The data in this research wasprocessed using SPSS (Statistical Package for Social Sciences) with Logistic Linear Regressionmethod. This research shows that tax compliance have a significant influence to the defender businessstrategy and tax avoidance do not have influence to the defender business strategy.